Postural changes in plasma renin activity and responses to vasoactive drugs in a case of Shy-Drager syndrome. - Mathias, C J (1977)
A male aged 47 years with gross autonomic insufficiency as part of the Shy-Drager syndrome is described. He did not sweat normally when warmed, and his circulatory responses to mental arithmetic, the Valsalva manoeuvre, and head-up tilt were abnormal indicating severe sympathetic failure. During head-up tilt there was a rise in plasma renin activity and plasma aldosterone. It is argued that plasma renin activity is not dependent on sympathetic nervous activity and may be mediated by renal baroreceptors. These rises may help sustain the blood pressure in such patients during repeated head-up tilts. Infusions of L-noradrenaline and angiotension produced greater hypertension, and injections of isoprenaline greater hypotension than in controls. Although it is difficult to exclude the possibility that one factor in this may be hypersensitivity of receptors in blood vessel walls, the principal factor is likely to be the absence of those baroreflexes of which the efferent pathways are in the sympathetic nervous system.